Grouting Defect Detection of Lapped Bar Connections Based on Impact-Echo Method. (14th October 2019) - Liu, Yun-Lin; Shi, Jing-Jing; Huang, Jun-Qi; Wei, Guang-Shuo; Wu, Zhi-Xin
Abstract : Grouted lap-splice connections are widely used for connecting precast concrete components. Grouting defects in the connections significantly influence the structural performance of the whole connection, which leads to the need for grouting defect detection. In this study, the impact-echo (IE) method was used for detecting defects in grouted lap-splice connections. Grouted connections with different levels of artificial grout defects were prepared in a shear wall, and the IE method was used to measure the frequency response. In addition, finite element (FE) analysis based on ABAQUS was conducted to simulate the tests. Based on the validated FE model, a parametric study was conducted to investigate the effect of the depth of the grout hole on the amplitude spectrum. The results indicated that (1) the IE method offered a good potential for grouting defect detection in grouted lap-splice connections; (2) the proposed FE model could well predict the frequency response of the grouting hole; and (3) the measured frequency and amplitude of the grouting hole in an impact-echo test would be considerably influenced by the hole depth.